A review: study on synthesis of biodiesel from waste cooking oil using nanohybrid catalyst with low methanol to oil ratio / Nurul Syafiqah Hamran and Prof. Madya. Dr Abdul Hadi Zainal - Hamran, Nurul Syafiqah; Zainal, Abdul Hadi (2020)
Biodiesel can act as an alternative fuel to reduce the emission level of some pollutant. Manufacturing biodiesel from Waste Cooking Oil (WCO) is one of another successful way to reduce the cost of raw materials and has many environmental benefits. However, the sustainable of biodiesel production is quiet challenging due to difficulty in securing cheap raw material. To reduce the cost, low ratio of methanol to oil used is suggested to limit the methanol user but the influence and effect to the yield need to study. This literature study aim were to determine on the yield of biodiesel synthesis from waste cooking oil using heterogeneous (nanohybrid) catalyst with low methanol to oil ratio by transesterification process and to determine the suitable ratio of low methanol to oil and the highly reactive nanohybrid catalyst which lead to high yield of biodiesel. For this study review, the online researches of the synthesis biodiesel yield by heterogeneous (nanohybrid) catalyst and the effect on the molar ratio methanol to oil data was collected from the relevant publish papers to compare the yield of biodiesel produce and their effect to the molar ratio methanol to oil. When the data processing is complete, the detail were go through and known as data analysis to make discussion and conclusion. Result obtained proved that nanohybrid catalyst can produce high yield of biodiesel above 90% in low ratio of methanol to oil. A very synergetic effect was noted in catalytic activity when hybrid (mixed) catalyst was used. The suitable low molar ratio of methanol to oil is 6:1 compare to 3:1 since stoichiometric molar ratio of alcohol to oil for the transesterification is 3:1. The biodiesel properties such density, flash point and kinematic density are following the ASTM D-6751 and EN-14214 requirement.